Effect of Annealing on Creep Behavior, Hardness, Roughness and Electrochemical Corrosion Parameters of Co- Cr Based Alloy (JOURNAL OF ADVANCES IN PHYSICS, 2017)
In the present work, the effect of annealing on creep behavior, hardness, maximum shear stress, roughness and electrochemical corrosion parameters of commercial Co64Cr29Mo6.5A0.5 (A= C, Si, Fe, and Mn) dental alloy from Travagliato (BS) - Italy have been studied and analyzed.  Creep behavior was studied by indentation and stress exponent was determined by Mulheam-Tabor method.  The results show that, Vickers hardness of Co64Cr29Mo6.5A0.5 alloy decreased but roughness parameters varied after annealing for two hours at 700, 800 and 900 -°C.  Also the corrosion resistance in 0.5M HCl of Co64Cr29Mo6.5A0.5 alloy is increased but the corrosion rate with 0.5M HCl is decreased after annealing compared to normal alloy.